Analysis of Rent, Buy and Rent-to-Buy With Net Present Value Method in the Decision of Truck Procurement at PT. XYZ - Safa'at, Safa'at; Nuzulul Fatimah; Dewi Kartikaningsih (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
PT. XYZ is a company engaged in ready-mix or ready-made concrete. This study aimed to analyze procurement decisions with several alternatives: rent, buy and lease, by applying the NPV (Net Present Value) method. The method was interviewing employees based on their fields and collecting the required documents. From the data analysis and evaluation carried out, then it decided to procure the truck. From the results of the study, it can be concluded that with the analysis of the NPV method, the decision to procure trucks was with a rent-to-buy model.